Empirical Analysis of Factors Responsible for Effective Student-Centred Education Framework - Menoja Nathaniel Akokaike; Christopher O. Ewhrudjakpo (Researchparks Publishing, 2022)
The research investigated the factors responsible for effective students-centered education framework, using primary data. The study was motivated by the fact that student-centered education framework has not been fully practiced to yield the needed returns our education system requires, despites government’s effort at different times to improve the standard and quality of education. The specific objectives included to determine whether cultural and social belief system is a reason for effective student-centered educational framework in public secondary schools, whether schools architecture and infrastructure is a reason for effective student-centered educational framework in public secondary Schools, whether duration of teaching period is a reason for effective student-centered educational framework in public secondary schools, whether motivation for teachers is a reason for effective student-centered educational framework in public secondary schools, whether teaching load is a reason for effective student-centered educational framework in public secondary schools; and whether class size is a reason for effective student-centered educational framework in public secondary schools. The study employed descriptive survey design. Data collected from the field were analyzed, by the researchers using Pearson's Correlation Moments. The Findings indicated that classroom architectures and infrastructure, teaching period, social and cultural belief system have positive and significant relationship with effective student-centered education framework. It was concluded that Student-centered education framework is imperative as major commanding height to attain effective learning. It was recommended that standard classroom architecture with smart technology should be initiated in schools by government and/or through public-private partnership. In addition, teachers should be adequately and timely incentivized with adequate provision of e-learning tools to teachers such as laptops, internet connectivity in schools with stable and quality electricity supply in schools. In the same vein, more teachers especially, mathematics and science teachers should be recruited and evenly posted or distributed across the State in order to mitigate heavy teaching load and large class size and lopsidedness.